Implicit and Explicit Iterative Methods for Systems of Variational Inequalities and Zeros of Accretive Operators - Lu-Chuan Ceng; Saleh Abdullah Al-Mezel; Qamrul Hasan Ansari (Abstract and Applied Analysis)
Based on Korpelevich's extragradient method, hybrid steepest-descent method, and viscosity approximation method, we propose implicit and explicit iterative schemes for computing a common element of the solution set of a system of variational inequalities and the set of zeros of an accretive operator, which is also a unique solution of a variational inequality. Under suitable assumptions, we study the strong convergence of the sequences generated by the proposed algorithms. The results of this paper improve and extend several known results in the literature.